Why Do We Persist with Traditional Classes of Anatomy in Chile in 2024? a Brief Communicationticoparasimpáticos, Ha Llegado el Momento de Clasificar el Sistema Autónomo en Función de la; [¿Por Qué en Chile, en el Año 2024 Aún Seguimos Con Las Clases Tradicionales en Las Asignaturas de Anatomía? Una Comunicación Breve] - Sanchez-Ramirez, C (Universidad de la Frontera, 2025)
This paper aims to make a metacognitive exercise about how we teach Anatomy subjects in Chile, from a critical reflective process to a deep practical understanding of our daily work. For this, a text that conflicts two visions is developed. On the one hand, the idea that teachers should use active methodologies to achieve deep learning has become widespread. On the other hand, traditional expository classes are outdated for the training of 21st century professionals. Despite the large number of studies that have been developed in Chile and the world, it is common to find in them that the variables studied are related to satisfaction, motivation and expectations, measured in all cases through questionnaires or qualitative methodologies in which many times those who respond do not represent the sample subjected to the methodological change. In no case is the most important thing measured: learning. © 2025, Universidad de la Frontera. All rights reserved.